3D Experiential Marketing in International Industrial Fair - Hung, Chao-Chih; Su, Min-Jiun; Zhuang, Wen-Long (Journal of Economics and Behavioral Studies, 2016)
This study explores the effect of buyers’ 3D experiences on their purchase intention, as well as the moderating effect of exhibitors’ corporate image on the above relationship. This study uses the purposive sampling method to survey buyers of the famous International Woodworking Machine Fair in China. Analytical results from 91 visitors are summarized as: the higher the international mechanical fair buyers’ feel experience, think experience and act experience, then the higher their purchase intention; buyers’ relate experience has a negative prediction effect on purchase intention; exhibitors’ corporate image has a moderating effect on the relationship between buyers’ feel experiences and purchase intention; exhibitors’ corporate image has a moderating effect on the relationship between buyers’ relate experience and purchase intention.